An International Finance Perspective to AfCFTA: The Relationship between Financial Development, Foreign Direct Investment, and Trade Liberalization with Economic Growth in Africa - Obijama, Obioma Chidiebere (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
While protectionism is on the rise around the world, 54 of 55 African countries signed an agreement called the Africa Continental Free Trade Area (AfCFTA) in July 2019, to integrate the economies of countries in Africa, and drive it towards peace and prosperity. This research used the FMOLS/DOLS tests and Dumitrescu-Hurlin Panel Granger based Causality technique to illustrate the long-term effects of some significant international finance elements on economic growth in Africa, particularly financial development, FDI, and trade liberalisation. The intention is to draw attention to how these elements may affect the free trade agreement's goal from the outset. The results obtained confirm that the proxies of trade liberalization, financial development, and FDI have a positive and significant long term influence on economic growth. Also the Dumitrescu-Hurlin panel Granger based Causality test point towards a bidirectional relationship between economic growth and FDI, and financial development and economic growth in Africa. The Granger Causality relationship between trade liberalization is unidirectional, flowing from trade liberalization to economic development.

ÖZ : Dünya genelinde korumacılığın arttığı bir dönemde, Temmuz 2019'da, 55 Afrika ülkesinin 54'ü, ekonomilerini entegre etmek ve kıtayı barış ve refaha yönlendirmek amacıyla Afrika Kıtasal Serbest Ticaret Alanı (AfCFTA) adlı bir anlaşma imzaladı. Bu araştırma, özellikle finansal kalkınma, doğrudan yabancı yatırım (DYİ), ve ticaret serbestleşmesi gibi önemli uluslararası finans unsurlarının Afrika'daki ekonomik büyüme üzerindeki uzun vadeli etkilerini göstermek amacıyla FMOLS/DOLS ve Dumitrescu-Hurlin Panel Granger Nedensellik testi tekniklerini kullanmıştır. Bu unsurların, serbest ticaret anlaşmasının hedefini başlangıçtan itibaren nasıl etkileyebileceğine dikkat çekme niyeti taşınmaktadır. Elde edilen sonuçlar, ticaret serbestleşmesi, finansal kalkınma ve DYİ'nin ekonomik büyüme üzerinde pozitif ve anlamlı uzun vadeli bir etkisi olduğunu doğrulamaktadır. Aynı zamanda, Dumitrescu-Hurlin panel Granger Nedensellik testi, Afrika'da ekonomik büyüme ile DYİ arasında ve finansal kalkınma ile ekonomik büyüme arasında karşılıklı bir ilişki olduğuna işaret etmektedir. Ticaret serbestleşmesi ile ekonomik gelişme arasındaki Granger Nedensellik ilişkisi ise tek yönlü olup, ticaret serbestleşmesinden ekonomik gelişmeye doğru yönelmektedir.
Master of Business Administration. Institute of Graduate Studies and Research. Thesis (M.B.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2024. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Thesis Tez; Business and Economics Department; Economic Conditions and Development--Economic Growth--Africa; Economic aspects--Africa; AfCFTA; free trade agreement; financial development; FDI; trade liberalization; foreign direct investment.